2018
DOI: 10.1111/cdev.13108
|View full text |Cite
|
Sign up to set email alerts
|

Echoes of Early Life: Recent Insights From Mathematical Modeling

Abstract: In the last decades, developmental origins of health and disease (DOHaD) has emerged as a central framework for studying early‐life effects, that is, the impact of fetal and early postnatal experience on adult functioning. Apace with empirical progress, theoreticians have built mathematical models that provide novel insights for DOHaD. This article focuses on three of these insights, which show the power of environmental noise (i.e., imperfect indicators of current and future conditions) in shaping development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 123 publications
(190 reference statements)
0
19
0
1
Order By: Relevance
“…Extensive previous research has suggested that children raised in noisy and unpredictable home environments show atypical responses within both subdivisions of the ANS (Basner et al., ; Bremmer et al., ; Evans & Wachs, ). Our finding that these relationships can be identified earlier in development than had previously been appreciated is novel, but unsurprising: extensive evidence suggests that early development is highly sensitive to environmental influence (Frankenhuis et al., ). Similarly novel, but theoretically predicted (Wass, ), is our finding that environmental influences on autonomic function affect performance in both cognitive, and affective, domains.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Extensive previous research has suggested that children raised in noisy and unpredictable home environments show atypical responses within both subdivisions of the ANS (Basner et al., ; Bremmer et al., ; Evans & Wachs, ). Our finding that these relationships can be identified earlier in development than had previously been appreciated is novel, but unsurprising: extensive evidence suggests that early development is highly sensitive to environmental influence (Frankenhuis et al., ). Similarly novel, but theoretically predicted (Wass, ), is our finding that environmental influences on autonomic function affect performance in both cognitive, and affective, domains.…”
Section: Discussionmentioning
confidence: 61%
“…As a result of this, we understand little of the mechanisms through which noise exposure affects emotional and cognitive performance. Further, most previous research into household noise has examined children and adults – rather than infants, who potentially are highly sensitive to environmental influences during early development (Frankenhuis, Nettle, & McNamara, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we suggest that the developmental trajectory of paranoia reflects a selective process that balances sensitivity to threat in line with fitness-relevant outcomes. (84)(85)(86)(87)(88). It has been suggested that adolescence could be one such sensitive period in development (84,89,90), with the evolutionary relevance being that individuals receive more reliable cues about the kind of social world they will inhabit and their place in it during adolescence than earlier in development (see (84)).…”
Section: Predictions Deriving From a Coalitional Psychology Model Of mentioning
confidence: 99%
“…The harshness-prosociality associations outlined by Life History Theory may have proven so difficult to pin down empirically because researchers have sought to measure the relevant features of the childhood environment solely in terms of exposure to poverty, violence, and neglect rather than in terms of exposure to abundance, care, and solicitous attention. A key insight from Bayesian developmental modeling is that humans may be sensitive to cues that the environment is safe (and amenable to prosociality), rather than exclusively sensitive to cues that the environment is harsh (Frankenhuis, Nettle, & McNamara, 2018). Bayesian models of development formally predict that people's behavioral trajectories (i.e., the likelihood of engaging in a given behavior over time) in environments that are rich with cues to safety will follow a unique mathematical function, relative to people's behavioral trajectories in environments abundant with cues to harshness (Stamps & Krishnan, 2014).…”
Section: Enriched Environments and Adult Charitable Givingmentioning
confidence: 99%